HPLC Analysis Mangostin After Orally Administration in Rats - Syamsudin; Faizatun; Rahayu, Lestari (Asian Journal of Chemistry, 2010)
A simple sensitive isocratic method for the detection and quantification of mangostin in plasma has been developed. The assay consisted of reversed-phase HPLC with ultraviolet detection. Separation was achieved on a C18 reversed-phase column. The mobile phase consisting of methanol and water (95:5 % v/v) was delivered at a flow rate of 1.0 mL/min. The assay was shown to be linear over the range 4-100 μg/mL (r ³ 0.9998). The HPLC analysis has been successfully applied to pharmacokinetic studies of mangostin after oral administration at a dose 40 mg/ kgbwt to rats. The main pharmacokinetic parameters were: t1/2 7.24 h; K el 0.058/h; tmax 62.99 min; Cmax 4.79 μg/mL; AUC 702.45 μg min/mL, respectively.